2011
DOI: 10.5144/1658-3876.2011.73
|View full text |Cite
|
Sign up to set email alerts
|

Very late onset lymphoproliferative disorders occurring over 10 years post-renal transplantation

Abstract: Older renal transplant patients are at increased risk for development of very late onset PTLD, and should be strictly followed. further multi-institutional prospective studies are needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…The histological types were Burkitt lymphoma, diffuse large B cell lymphoma, and Hodgkin-type PTLD. Though all individual cases were unique in their presentation, our series reflected the heterogenous presentation of late PTLDs that was described in other published case reports and series [1,5,7].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The histological types were Burkitt lymphoma, diffuse large B cell lymphoma, and Hodgkin-type PTLD. Though all individual cases were unique in their presentation, our series reflected the heterogenous presentation of late PTLDs that was described in other published case reports and series [1,5,7].…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, recent studies have proposed that earlyand late-onset PTLD affect different populations, have different morphologic characteristics, and have different behaviors [2,3,5]. Because our cases are examples of late-onset PTLD, we will focus on this subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases can take more than 10 years, and investigators have introduced a new category for cases with onset of more than 10 years between transplantation and PTLD appearance: very late onset. It represents a distinct clinicopathological subset, occurring more frequently in older patients with a long latency period, EBV-negativity, and with poor response to treatment and worse prognosis [4]. Our case fits in this rare category, as the patient was EBV-negative, developed lymphoma after almost a decade of transplantation, and had a poor outcome.…”
Section: Discussionmentioning
confidence: 61%
“…In the current study, 2 of our findings might be considered predictors for a better outcome for CD20-positive PTLD patients: the higher share of early onset PTLD and the lower rate of bone marrow involvement. However, a previous study of ours showed no survival advantage for early onset PTLD in renal recipients, 50 but bone marrow involvement was a predictor for lower outcome (unpublished data). Our finding about the inferior outcome of PTLD in renal recipients expressing the CD20 antigen on their tumor cells cannot be explained by simultaneous characteristics and seems to be independent.…”
Section: Discussionmentioning
confidence: 75%